SKIN PERMEATION ENHANCEMENT EFFECTS OF ASCORBIC ACID AND TRIETHYL CITRATE ON ROFECOXIB - MALAY K. DAS; ABDUL B. AHMED (Universiti Sains Malaysia, 2008)
The enhancing effect of ascorbic acid and triethyl citrate (TEC) on the in vitro skin permeation of rofecoxib across rat epidermis was investigated. Skin pre-treatment with ascorbic acid and TEC at different concentrations, followed by application of rofecoxib gel, showed higher permeation flux than the control condition. The mechanism underlying this permeation enhancement was probed with fourier transform infrared spectroscopy (FTIR). The FTIR spectra of rat epidermis treated with ascorbic acid revealed that ascorbic acid at low concentration appears to interact with dermal keratin, whereas at higher concentration it appears to interact with both dermal proteins and lipids. The FTIR spectra of rat epidermis treated with TEC showed a decrease in peak heights for both asymmetric and symmetric C-H stretching absorbance, indicating a change in the fluidity of alkyl chains in the intercellular lipids in the stratum corneum (SC). The protein disruption effect of TEC was probably due to the solvation of keratin by the formation of hydrogen bonds between TEC hydroxyl groups and keratin chain C=O groups. Skin pre-treatment with different concentrations of permeation enhancers did not show any significant change in lag time in comparison to control. The amount of rofecoxib retained in the skin after skin pre-treatment with enhancers was found to be higher than in the experiment without skin pre-treatment. Scanning electron microscopy (SEM) confirmed the maintenance of skin integrity throughout the permeation experiment. The observed permeation enhancing effects of ascorbic acid and TEC in the present study indicate that a rapid percutaneous absorption of rofecoxib at effective therapeutic levels may facilitate faster anti-inflammatory activity.